2006
DOI: 10.7589/0090-3558-42.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Clostridium Botulinum Type E Neurotoxin to Great Lakes Fish: Implications for Avian Botulism

Abstract: ABSTRACT:Since 1999, large-scale mortalities of fish-eating birds have been observed on the Great Lakes, and more specifically on Lake Erie. Type E botulism has been established as the primary cause of death. The mechanism of type E botulism exposure in fish-eating birds is unclear. Given that these birds are thought to eat live fish exclusively, it seems likely that their prey play a key role in the process, but the role of fish as potential transport vectors of botulinum neurotoxin type E (BoNT/E) to birds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…Because many fish in our study were alive, even when harboring free toxin (i.e., in the positive BoNT/E nonfillet samples), our results suggest that similarly affected wild fish could represent a vector for BoNT/E transfer to fish-eating birds in nature. Other work in our lab (14,15) has confirmed that fish can survive for prolonged periods, even after consuming relatively high-and ultimately lethal-doses of toxin. The present study verifies that at least some of this toxin can be present as free toxin in affected fish, either during the living morbidity phase or after death.…”
Section: Public Health Implications the High Proportion Ofmentioning
confidence: 64%
See 2 more Smart Citations
“…Because many fish in our study were alive, even when harboring free toxin (i.e., in the positive BoNT/E nonfillet samples), our results suggest that similarly affected wild fish could represent a vector for BoNT/E transfer to fish-eating birds in nature. Other work in our lab (14,15) has confirmed that fish can survive for prolonged periods, even after consuming relatively high-and ultimately lethal-doses of toxin. The present study verifies that at least some of this toxin can be present as free toxin in affected fish, either during the living morbidity phase or after death.…”
Section: Public Health Implications the High Proportion Ofmentioning
confidence: 64%
“…The majority of fish expressed clinical signs that included equilibrium loss, pigmentation change, respiratory distress, and erratic swimming. A description of the onset of clinical signs and the number of fish expressing clinical signs is outlined in Yule et al (14). After death (as a result of BoNT/E intoxication, or, in the case of fish surviving to 10 days, by an overdose of tricaine methanesulfate MS-222), experimental fish were immediately double bagged and frozen at Ϫ20ЊC in a conventional freezer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can detect BoNT at levels comparable with or lower than levels detected with mouse bioassays. 1,2,[15][16][17] The use of fish bioassays to establish LD 50 s and sensitivities for botulinum has been described, 6,25,26 but no fish neutralization bioassays have been reported. This manuscript reports a catfish neutralization bioassay confirmed by Endopep-MS to link botulinum in the syndrome of VTC.…”
Section: Discussionmentioning
confidence: 99%
“…The round goby is a benthic fish that feeds on benthic organisms, including filter-feeding bivalves (8,10,21), and would therefore be exposed to bacteria, such as C. botulinum type E, that are found in lake sediments. One study (37) on round gobies that were experimentally intoxicated with type E botulinum toxin found that the fish exhibited pigmentation changes and displayed erratic swimming behavior. A reasonable hypothesis is that such changes make intoxicated fish easier prey for a piscivorous bird.…”
Section: Discussionmentioning
confidence: 99%